2015
DOI: 10.1038/srep13131
|View full text |Cite
|
Sign up to set email alerts
|

Histamine deficiency exacerbates myocardial injury in acute myocardial infarction through impaired macrophage infiltration and increased cardiomyocyte apoptosis

Abstract: Histamine is a biogenic amine that is widely distributed and has multiple functions, but the role it plays in acute myocardial infarction (AMI) remains unclear. In this study, we investigated the origin and contribution of endogenous histamine to AMI. Histidine decarboxylase (HDC) is the unique enzyme responsible for histamine generation. Using HDC-EGFP bacterial artificial chromosome (BAC) transgenic mice in which EGFP expression is controlled by the HDC promoter, we identified HDC expression primarily in CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 52 publications
5
45
3
1
Order By: Relevance
“…A previous study demonstrated that cardiomyocyte apoptosis in the infarcted hearts markedly increased in HDC −/− mice than WT mice during the early stages of MI10. However, in this study we observed that there was no significant difference in the degree of cardiomyocyte apoptosis in HDC −/− mice compared with WT mice at 4 weeks post-MI (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 59%
“…A previous study demonstrated that cardiomyocyte apoptosis in the infarcted hearts markedly increased in HDC −/− mice than WT mice during the early stages of MI10. However, in this study we observed that there was no significant difference in the degree of cardiomyocyte apoptosis in HDC −/− mice compared with WT mice at 4 weeks post-MI (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 59%
“…The percentage of apoptotic cells in the salivary glands was enhanced in rats with ligature‐induced periodontitis as compared to that in the control rats (Nakamura‐Kiyama et al , ). Histamine reduces cell apoptosis (Deng et al , ), and accordingly, periodontitis‐induced increase in the proportion of apoptotic cells in rat submandibular gland (SMG) could be reduced by histamine treatment (Prestifilippo et al , ). Apoptosis in SMG might also be induced by depleted level of oxidative stress (OS) markers in the serum of patients with periodontitis (Ekuni et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that mast cells are the main source of histamine release in response to injury and wound healing . However, using Hdc ‐EGFP transgenic mice, previous studies revealed that CD11b + Gr‐1 + myeloid cells were the major HDC‐expressing cells in inflammation‐associated tumorigenesis and myocardial infarction . This suggests that mast cells in tissues may play a role in the temporary storage of histamine derived from these HDC‐expressing cells, such as basophils and CD11b + Gr‐1 + myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gastric enterochromaffin‐like cells, histaminergic neurons, mast cells and basophiles are important cellular sources of histamine. Interestingly, recent studies reported that HDC is highly expressed in CD11b + Gr‐1 + immature myeloid cells within the bone marrow and spleen, and these HDC‐expressing CD11b + immune cells can be activated and recruited to inflammatory tissues . Histamine is involved in the regulation of inflammation, hematopoiesis, immune cell differentiation, embryonic development and wound healing, but its roles in the proliferation and differentiation of muscle stem cells and tissue regeneration have not been fully studied.…”
Section: Introductionmentioning
confidence: 99%